1991
DOI: 10.1038/hdy.1991.24
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation between sympatric Killer whale populations

Abstract: The genetic variation within and between putative Killer whale (Orcinus orca) populations was examined by DNA fingerprinting nuclear genomes and sequencing the D-loop region of the mitochondrial genome. Mitochondrial DNA variation indicated that two sympatric populations in the northeastern Pacific were as genetically distinct as North Pacific populations from a South Atlantic population. The two sympatric populations are known to pursue different foraging strategies. DNA fingerprinting showed very low levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 16 publications
4
69
0
2
Order By: Relevance
“…In particular, the DNA fingerprinting technique is extremely sensitive and revealed a substantial amount of genetic variation in two populations of the African cheetah while none had been detected by allozyme electrophoresis (Gilbert et a!., 1991). Moreover, DNA fingerprinting has been able to provide insight in the genetic structure of populations with low levels of genetic variation (Reeve et a!., 1990;Hoelzel & Dover, 1991;van Pijien et al, 1991;Brock & White, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the DNA fingerprinting technique is extremely sensitive and revealed a substantial amount of genetic variation in two populations of the African cheetah while none had been detected by allozyme electrophoresis (Gilbert et a!., 1991). Moreover, DNA fingerprinting has been able to provide insight in the genetic structure of populations with low levels of genetic variation (Reeve et a!., 1990;Hoelzel & Dover, 1991;van Pijien et al, 1991;Brock & White, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Field studies in waters around Vancouver Island, British Columbia (Canada), during the 1970s revealed the existence of 2 sympatric forms that differed in morphology, behaviour and movement patterns (Bigg et al 1976, Bigg 1982, Bigg et al 1990). Termed 'residents' and 'transients' based on their apparent fidelity to the study area, they are now known to be reproductively isolated and genetically distinct lineages (Stevens et al 1989, Hoelzel & Dover 1991, Barrett-Lennard 2000 that differ markedly in social dynamics (Ford & Ellis 1999, Baird & Whitehead 2000, vocal behaviour (Ford & Fisher 1982, Barrett-Lennard et al 1996, Deecke et al 2005) and foraging strategy. Resident killer whales feed exclusively on teleost fish and squid, especially Pacific salmon Oncorhynchus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the northeastern PaciWc Ocean, killer whale abundance and population biology has been well documented at longterm study sites in Prince William Sound, southeastern Alaska, British Columbia, and Puget Sound Olesiuk et al 1990;Dahlheim et al 1997;Ford et al 2000). These studies have documented three sympatric forms (or ecotypes) of killer whales, named 'residents', 'transients', and 'oVshores', which diVer in morphology, ecology, behavior, and genetics ; Baird and Stacey 1988;Hoelzel and Dover 1991;Matkin and Saulitis 1994;BarrettLennard et al 1996;Ford et al 1998Ford et al , 2000Hoelzel et al 1998;Baird 2000). Notably, these ecotypes diVer markedly in their feeding specializations, with residents being primarily Wsh-eaters in contrast to transients that feed mainly on marine mammals (Ford et al 1998;Saulitis et al 2000;Herman et al 2005).…”
Section: Introductionmentioning
confidence: 99%